Management of high-output cardiac failure caused by head and neck AVMs: Percutaneous suture-assisted ethanol and coil embolotherapy - Wen, Ming-zhe; Li, Xin-yu; Shen, Yu-chen; Wang, Zhen-feng; Zheng, Lian-zhou; Wang, De-ming; Fan, Xin-dong; Su, Li-xin; Yang, Xi-tao (Frontiers in Cardiovascular Medicine, 2022)
Purpose The aim of this study was to describe the treatment technique, outcomes, and complications of Schobinger stage IV head and neck arteriovenous malformations (HNAVMs) with associated high-output cardiac failure (HOCF) using ethanol and coils with the percutaneous suture technique. Methods From January 2015 to December 2019, 19 patients who had HNAVMs with associated HOCF were treated first with a percutaneous suture of the remarkably dilated dominant drainage vein (RDDOV) and subsequent embolization with coils and ethanol. The percutaneous suture of RDDOV was preferred to be performed, followed by the deployment of coils and the injection of absolute ethanol via transarterial approach, direct puncture approach, or both of them. Treatment outcomes and complication rates were evaluated at follow-up. Results A total of 19 patients who experienced HNAVMs with HOCF received 19 percutaneous suture procedures and 84 embolization procedures with ethanol and coils. Complete or >90% shunt reduction of the AVM was achieved in 16 patients. Notably, 19 patients with New York Heart Association (NYHA) stage II improved to stage I, and the symptom of dyspnea disappeared after embolization. The symptoms of five patients with bleeding disappeared. All patients presented with cosmetic concerns; Four were cured, and eight had a clearly recognizable improvement. Of note, 19 (100%) patients presented with impairment of daily life, which was resolved. The minor complications were encountered and recovered by the self. No major complications occurred. Conclusion This study provides evidence that ethanol and coil embolotherapy is effective and safe in treating HOCF caused by HNAVMs with acceptable complications in these cases. The percutaneous suture technique for RDDOV management can act as an adjunct for embolotherapy.